The perceptions, attitudes and knowledge of physiotherapy and chiropractic students regarding each others' professional practice - N. Naidoo; L. Bühler (AOSIS, 2009)
Introduction: The roles of physiotherapists and chiropractors demon-strate some overlap. Both are members of a multidisciplinary team and contributeto the holistic care of patients. Good understanding of each others' professionalpractice may lead to good working relationships with effective referrals, inter -disciplinary and multidisciplinary management of patients. Purpose: To investigate the perceptions, attitudes and knowledge of undergraduatephysiotherapy and chiropractic students about each others' professional roles inclinical practice. Methodology: Data was obtained using a questionnaire with closed and open-ended questions. First and ﬁnal-yearphysiotherapy (n = 72) and chiropractic students (n = 49) participated. Results: First and ﬁnal year physiotherapy students scored 58% and 62% respectively in the "test" on chiropractic;chiropractic students scored 52% and 68% respectively in the test on physiotherapy. Seventy percent of the chiropractic and 14% of the physiotherapy students had visited the practice of other profession. Sixty seven percent of the chiropractic and 38% of the physiotherapy students found it was effective. Forty seven percent chiropractic and 80% physiotherapy students considered physiotherapy and chiropractic to be in direct competition. Sixty six percentof the chiropractic students and 49% of the physiotherapy students expressed the intention of working together withthe other profession.  Discussion: The reason for the possible feelings of competitiveness could be because in South A frica there is vastoverlap of practice in both professions; Physiotherapists and chiropractors are seen to use modalities that are similar.This may be viewed as an indication of the importance in deﬁning the roles, scope and characteristics of both physio-therapy and chiropractic.Conclusion: The knowledge of the physiotherapy and chiropractic students is equal, however, chiropractic studentshave more positive perceptions and attitudes towards physiotherapy than physiotherapy students have of chiropractic.